Islamic Education Financing Management: A Conceptual Analysis of the High Cost-Low Performance Phenomenon Based on Efficiency and Justice - Annisa Prawati Ningrum (Edudeena : Journal of Islamic Religious Education, 2025)
The increasing cost of education that is not accompanied by an increase in educational performance reflects a fundamental problem in the management of educational financing, particularly in Islamic educational institutions. This article aims to conceptually analyze the phenomenon of high cost–low performance in Islamic educational financing, emphasizing the principles of efficiency, effectiveness, and equity. This research uses a qualitative approach through literature review and conceptual analysis of academic books, journal articles, and policy documents relevant to educational financing. The analysis shows that high educational costs are not solely caused by limited funding sources, but also by inefficient budget allocation, weak financial governance, minimal performance-based budgeting, and the existence of indirect and hidden costs that burden students and the community. Furthermore, financing practices that do not pay attention to the principle of equality have the potential to widen the gap in access and quality of education, especially for lower socioeconomic groups. From the perspective of Islamic education, educational financing is a mandate that must be managed efficiently, fairly, transparently, and oriented towards the welfare of the community. This article emphasizes the importance of reforming Islamic education financing management that integrates the principles of efficiency, effectiveness, fairness, and stakeholder participation as the basis for formulating sustainable education financing policies that are oriented towards improving the quality of education.